Easy asteroid phase curve fitting for the Python ecosystem: Pyedra - Colazo, Milagros Rita (2022)
A trending astronomical phenomenon is the variation in brightness of asteroids. This can be caused by its rotation on its own axis and/or its position relative to the sun. The latter behavior can be visualized on a phase curve, which shows the reduced magnitude as a function of the phase angle. To enable the comparison between several models for the dependence of reduced magnitude on phase angle we present a Python package called Pyedra. Pyedra implements three phase-curve-models, and also provides tools for visualization as well as integration with external datasets. The package is fully documented and tested following a strict quality-assurance workflow, with a user-friendly programmatic interface. In future versions, we will include more models, and additional estimation of quantities derived from parameters such as diameter and different albedos, and correlation of information of physical and orbital parameters.